2000
DOI: 10.1046/j.1469-0705.2000.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between congenital heart disease and Down syndrome in prenatal life

Abstract: We have confined that more than half of the fetuses with DS bear a CHD, which is an AVSD in 44% of cases. Conversely, 43% of fetuses with an AVSD have trisomy 21. For VSDS, the situation is controversial, due to the relatively low detection level of this heart defect at the routine mid-trimester obstetric scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 17 publications
(23 reference statements)
7
72
1
2
Order By: Relevance
“…A study by Paladini and colleagues 43 suggested what is possible under ideal conditions. Scanning at an optimal gestational age (24 weeks), under optimal conditions (in a dedicated fetal echocardiographic center), with inclusion of subtle ventricular septal defects, and with previous knowledge of fetal karyotype, they were able to detect heart defects in just more than half of fetuses with Down syndrome.…”
Section: Trisomy 21mentioning
confidence: 99%
“…A study by Paladini and colleagues 43 suggested what is possible under ideal conditions. Scanning at an optimal gestational age (24 weeks), under optimal conditions (in a dedicated fetal echocardiographic center), with inclusion of subtle ventricular septal defects, and with previous knowledge of fetal karyotype, they were able to detect heart defects in just more than half of fetuses with Down syndrome.…”
Section: Trisomy 21mentioning
confidence: 99%
“…3,4,6 These studies were performed in the 1990s, before the introduction of the first trimester screening in the clinical practice.…”
Section: Commentmentioning
confidence: 99%
“…We found that although the rate of trisomy 21 is higher in the group of women with a high first trimester risk (>1:150) and an AVSD (70%, 95%CI: 52-83%), the absolute rate remains high in the group with a low first trimester risk (41%, 95% CI: 27-57%), a difference which does not vary significantly when the chosen threshold is 1:250 (66% versus 41%). In a previous study 3 conducted before the introduction of screening by NT and combined testing, the risk of trisomy 21 in fetuses with an AVSD was assessed by taking into account the age-related maternal risk and the relative risk was found to be 107. The authors concluded that with such a high relative risk, even in the presence of a very low first trimester risk (e.g.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The (birth) prevalence of CHDs in DS is about 40-60%, most frequently atrioventricular septal defects and ventricular septal defects. [6][7][8] Efforts have been made to determine the critical chromosomal region for specific phenotypic features of DS by deletion mapping and characterization of patients with partial trisomy 21. 4,9,10 One potential candidate gene for these trisomy 21-related CHDs is collagen type VI.…”
Section: Introductionmentioning
confidence: 99%